Persepsi pola asuh permisif terhadap kecenderungan cinderella complex pada mahasiswi rantau di Fakultas Psikologi Universitas Merdeka Malang - Nur Azizah; Al Thuba Septa Priyanggasari (Jurnal Psikologi Tabularasa, 2021)
Cinderella complex makes individuals lose their optimal abilities, which can affect their role as overseas female students. The purpose of this study was to determine the effect of permissive parenting perceptions with Cinderella Complex in overseas female students at the Faculty of Psychology, University of Merdeka Malang. This research is a correlational quantitative research. The population were overseas female students from the Faculty of Psychology, University of Merdeka Malang in the odd semester of 2020-2021 (n = 104). The instruments used were the Cinderella Complex Scale (reliability = 0.788) and the Permissive Parenting Perception Scale (reliability = 0.899). Data analysis using simple linear regression correlation. Data analysis showed that there was a relationship between permissive parenting perceptions and the cinderella complex, with a positive relationship. The effect permissive parenting perceptions on cinderella complex in overseas female students at the Faculty of Psychology, University of Merdeka Malang was 15.8%. The relationship between permissive parenting perceptions with the tendency of Cinderella Complex can be minimized by increasing social activities that are not limited to the environment from the same area of origin to provide insight and build a more positive self-concept.